Preparation method of carbon dioxide adsorption block with porous structure
By preparing the carbon dioxide adsorption block with a porous structure, the problem of poor air flowability of solid amine materials during carbon dioxide adsorption is solved, and smoother flue gas flow and stronger carbon dioxide adsorption capacity are achieved.
Patent Information
- Application Number
- CN202411367025.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-02-25
AI Technical Summary
When existing solid amine materials are adsorbed with carbon dioxide, poor air circulation due to granular or powdery forms, increasing smoke exhaust resistance and affecting industry production.
The carbon dioxide adsorption block preparation method with a porous structure is adopted. By mixing the adhesive material and the carbon dioxide adsorption material evenly, extruding into a block shape, hot air is introduced so that it does not melt as a whole and sticks to each other, and then cooling is hot to form an adsorption block with a porous structure.
It improves air flowability, reduces smoke exhaust resistance, enhances the adsorption capacity of carbon dioxide, and allows flue gas to pass smoothly.
Smart Images

Figure CN119500074A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of gas adsorption, and in particular to a method for preparing an adsorption material. Background Art
[0002] Carbon neutrality and carbon peak are important measures to address global climate change and are of great significance for protecting the ecological environment and promoting green development. However, some high-energy-consuming industries, such as petroleum, coking, metal smelting, electricity and heat, consume a lot of energy, thus causing a large amount of flue gas emissions.
[0003] In recent years, solid amine materials, as a new type of carbon dioxide adsorbent, have the advantages of high selectivity, good adsorption performance and low corrosion to equipment in the capture and separation of carbon dioxide. They have become a research hotspot in the field of carbon dioxide adsorption removal and industrial decarbonization. However, the solid amine materials currently used are basically in granular or powdered form. When using granular or powdered solid amine materials for carbon dioxide adsorption, the air has poor air circulation when passing through the granular or powdered solid amine materials. Using adsorption equipment with poor air circulation in the smoke exhaust channel will increase the smoke exhaust resistance, resulting in unsmooth smoke exhaust and affecting industry production. Summary of the invention
[0004] The object of the present invention is to provide a method for preparing a carbon dioxide adsorption block having a porous structure, so as to solve at least one of the above technical problems.
[0005] The technical problem solved by the present invention can be achieved by adopting the following technical solutions:
[0006] A method for preparing a carbon dioxide adsorption block having a porous structure, the method comprising the following steps:
[0007] Step 1: Mix the bonding material and the carbon dioxide adsorbing material evenly;
[0008] Step 2: Extrude the block shape;
[0009] Step 3: Introduce hot air and blow until the adhesive material and the carbon dioxide adsorbent material are not melted as a whole but adhere to each other;
[0010] Step 4: After hot cutting, cooling is performed to obtain a carbon dioxide adsorption block with a porous structure.
[0011] In the above design, the role of the carbon dioxide adsorbent material is to adsorb carbon dioxide in the air, and the role of the adhesive material is to adhere the carbon dioxide adsorbent material. Therefore, the melting point of the adhesive material is lower than that of the carbon dioxide adsorbent material. When the two are mixed together, there are gaps between the carbon dioxide adsorbent materials, and these gaps allow air to pass through. The adhesive material is filled around the carbon dioxide adsorbent material. When heated, the adhesive material is in a semi-molten state, thereby bonding the carbon dioxide adsorbent material into a whole. The mitigation material that is not melted as a whole and is in a mutually adhered state is cut into granular porous materials through hot cutting. The beneficial effect is that when the granular materials with a porous structure are piled together, it is easier for flue gas to pass through, and the granular material with a porous structure has a stronger ability to adsorb carbon dioxide when flue gas passes through.
[0012] Further, the adhesive material is one or more of polypropylene, polyethylene, and rubber;
[0013] The bonding material is a powder material, and the diameter of the powder is 0.2 to 0.45 mm;
[0014] The carbon dioxide adsorbing material is one or more of a cross-linked primary amine resin and a polyethyleneimine resin;
[0015] The carbon dioxide adsorbent material may be in granular or powder form;
[0016] The diameter of the carbon dioxide adsorbent is 0.2 to 1.2 mm.
[0017] In the above design, the adhesive material is one or more of polypropylene, polyethylene, and rubber, which has the characteristic of softening when heated, and can adhere the carbon dioxide adsorbent material together in the softened state. The carbon dioxide adsorbent material uses a cross-linked primary amine resin or polyethyleneimine resin, both of which have the characteristics of large carbon dioxide adsorption and desorption capabilities. When the carbon dioxide adsorbent material is in powder form, the porosity of the formed mixed material is low, and when the carbon dioxide adsorbent material is in granular form, the porosity of the formed mixed material is high.
[0018] Furthermore, the amount of the carbon dioxide adsorbent material accounts for 10 to 90% of the mass of the carbon dioxide adsorbent block;
[0019] There are gaps between carbon dioxide adsorption materials, and the ratio of the gap volume to the volume of the carbon dioxide adsorption block is called porosity;
[0020] Different sizes of granular or powdered carbon dioxide adsorbent materials affect the porosity.
[0021] In the above design, the amount of carbon dioxide adsorbent material used is allowed to be between 10% and 90%. The more carbon dioxide adsorbent material is used, the better the adsorption and desorption effects are.
[0022] When the carbon dioxide adsorbent material and the adhesive material are mixed, there are gaps between the granular material and the powdered material. The larger the size of the granular material, the more gaps are left. Therefore, the porosity can be controlled by mixing carbon dioxide adsorbent materials and adhesive materials of different sizes.
[0023] Further, a granular or powdered carbon dioxide adsorbent material is selected according to the required porosity and mixed with a powdered binding material;
[0024] Hot air is blown into the mixed material at a temperature of 180-200°C and maintained for 10-40 seconds until the mixed material is in a state where it does not melt as a whole but sticks to each other.
[0025] In the above design, the beneficial effect of using hot air to fuse the two materials is that hot air can easily control the uniformity of heating, so that the mixed materials can be better adhered to each other without melting as a whole. The method of using hot air to promote the adhesion of carbon dioxide adsorbent material and adhesive material is called hot air forming method.
[0026] Furthermore, step 2 uses an extrusion device, which includes a mesh plate, and a hot air blowing port is arranged below the mesh plate;
[0027] The grid on the grid plate meets the size requirements of the outflow to meet the block outflow;
[0028] Laying evenly mixed carbon dioxide adsorbent material and adhesive material on the grid plate;
[0029] The laid mixed material is pressed downwards to squeeze the mixed material out of the grid;
[0030] Blow hot air on the extruded mixed material until the mixed material does not melt as a whole and sticks to each other;
[0031] A resistance wire is arranged below the mesh plate, and the resistance wire cuts through the lower part of the mesh plate in a heated state to perform thermal cutting on the extruded mixed material.
[0032] In the above design, a hot air blowing port is provided below the grid plate. After the mixed material is extruded from the grid of the grid plate, it quickly enters a state of not melting as a whole and sticking to each other under the action of the hot air. In this state, the carbon dioxide adsorbent material is adhered together by the adhesive material to form a carbon dioxide adsorbent block with a porous structure. When the heating resistance wire cuts through the mixed material that is not melting as a whole and sticking to each other in the heated state, it is easy to cut it flat to form a block material of the mixed material.
[0033] For further optimization, two heating resistor wires are used for hot cutting.
[0034] In the above design, two heating resistance wires cut the extruded mixed material, which can share the area swept by the cutting. The beneficial effect is that the hot cutting time is shortened and the hot cutting efficiency is improved.
[0035] For further optimization, the mesh of the grid plate uses circular holes;
[0036] The size of the circular hole is 4 to 6 mm;
[0037] The length of hot cutting is 3 to 4 mm.
[0038] In the above design, the beneficial effect of using circular holes in the grid is that it is easy to process and can reduce manufacturing costs.
[0039] Further optimization, a flexible plastic net is laid on the grid plate;
[0040] Laying evenly mixed carbon dioxide adsorbent material and adhesive material on the plastic net;
[0041] The mixed material laid on the plastic net is squeezed downward so that the plastic net wraps the mixed material and squeezes it out of the mesh;
[0042] A heating resistor wire is used to cut into the lower part of the mesh plate, and the mixed material wrapped with the plastic mesh is cut off and sealed at the same time.
[0043] In the above design, an elastic plastic net is laid on the grid plate, and the mixed material is laid on the plastic net. After hot cutting, the plastic net is coated on the outside of the mixed material. The beneficial effects are: firstly, after coating with the plastic net, the gaps between the blocks are increased, allowing air circulation to be smoother; secondly, the protection strength of the blocks is enhanced, making the blocks less likely to break; finally, the broken blocks can still maintain a block state under the coating of the plastic net, and will not break into tiny particles or even powder, resulting in blocking the gaps for air circulation.
[0044] Furthermore, the extrusion device includes a cavity for accommodating materials, and the cavity has a feed inlet and a discharge outlet;
[0045] A flat plate is also provided in the cavity, which moves toward the discharge port and is called an extrusion plate. A telescopic mechanism is connected to the back of the extrusion plate.
[0046] The discharge port is provided with a mesh plate;
[0047] A movable heating resistance wire is also arranged under the grid plate;
[0048] At least two hot air blowing ports are also arranged below the moving track of the heating resistance wire, and the at least two hot air blowing ports are symmetrically arranged.
[0049] In the above design, the aperture of the grid holes on the grid plate is used to limit the size of the block. The extrusion plate is driven by the telescopic mechanism to extrude the mixed material out of the grid holes. A hot air blowing port is provided on the outside of the grid plate. The two hot air blowing ports are symmetrically arranged, and the hot air is evenly distributed in the discharge port range. The extruded mixed material quickly enters a state of not melting as a whole and adhering to each other under the action of the hot air, so that the adhesive material adheres to the carbon dioxide adsorption material to form a block material with a porous structure.
[0050] Furthermore, the method for preparing the carbon dioxide adsorption block with a porous structure is prepared by adopting the method for preparing the carbon dioxide adsorption block with a porous structure as claimed in any one of claims 1 to 9.
[0051] The present invention bonds the carbon dioxide adsorbent material together through an adhesive material to form a block material with a porous structure. The beneficial effect is that when the granular materials with a porous structure are piled together, it is easier for flue gas to pass through. The granular materials with a porous structure have a stronger ability to adsorb carbon dioxide when flue gas passes through.
[0052] The block material is sealed by wrapping with an elastic plastic net, which has the beneficial effects of, firstly, increasing the gaps between the blocks after being wrapped with the plastic net, allowing air circulation to be smoother; secondly, enhancing the protection strength of the blocks, making the blocks less likely to break; finally, the broken blocks can still maintain their block state under the wrapping of the plastic net, and will not break into tiny particles or even powder, resulting in blocking the gaps for air circulation. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0054] Figure 1 It is a schematic diagram of a method for preparing a carbon dioxide adsorption block having a porous structure according to the present invention;
[0055] Figure 2 It is a schematic diagram of the extrusion device of the present invention.
[0056] Explanation of symbols:
[0057] 1. Extrusion plate; 2. Mixed material; 3. Grid plate; 4. Resistance wire; 5. Hot air blowing port; 6. Feed port; 7. Telescopic mechanism; 8. Carbon dioxide adsorption material; 9. Adhesive material; 10. Gap. DETAILED DESCRIPTION
[0058] In order to make the above-mentioned objects, features and advantages of the present invention more clearly understood, the specific implementation modes of the present invention are described in detail below in conjunction with the accompanying drawings.
[0059] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0060] Secondly, the present invention is described in detail with reference to schematic diagrams. When describing the embodiments of the present invention in detail, for the sake of convenience, the cross-sectional diagrams showing the device structure will not be partially enlarged according to the general scale, and the schematic diagrams are only examples, which should not limit the scope of protection of the present invention. In addition, in actual production, the three-dimensional dimensions of length, width and depth should be included.
[0061] Furthermore, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor is it a separate or selective embodiment that is mutually exclusive with other embodiments.
[0062] Reference Figure 1 As shown, a method for preparing a carbon dioxide adsorption block having a porous structure, the method for preparing a carbon dioxide adsorption block having a porous structure comprises the following steps:
[0063] Step 1: Evenly mix the bonding material 9 and the carbon dioxide adsorbing material 8;
[0064] Step 2: Extrude the block shape;
[0065] Step 3: Introduce hot air and blow until the adhesive material 9 and the carbon dioxide adsorbent material 8 are not melted as a whole but adhere to each other;
[0066] Step 4: After hot cutting, cooling is performed to obtain a carbon dioxide adsorption block with a porous structure.
[0067] In this embodiment, the carbon dioxide adsorbent material 8 is used to adsorb carbon dioxide in the air, and the adhesive material 9 is used to adhere the carbon dioxide adsorbent material 8. Therefore, the melting point of the adhesive material 9 is lower than that of the carbon dioxide adsorbent material 8. When the two are mixed together, there are gaps 10 between the carbon dioxide adsorbent materials 8, and these gaps 10 allow air to pass through. The adhesive material 9 is filled around the carbon dioxide adsorbent material 8. When heated, the adhesive material 9 is in a semi-molten state, thereby adhering the carbon dioxide adsorbent material 8 into a whole. The mitigation material that is not melted as a whole and adheres to each other is cut into granular porous materials by hot cutting. The beneficial effect is that when the granular materials with porous structures are piled together, it is easier for flue gas to pass through, and the granular materials with porous structures have a stronger ability to adsorb carbon dioxide when flue gas passes through.
[0068] Further, the adhesive material 9 is one or more of polypropylene, polyethylene, and rubber;
[0069] The bonding material 9 is a powder material, and the diameter of the powder is 0.2 to 0.45 mm;
[0070] The carbon dioxide adsorbent material 8 is one or more of a cross-linked primary amine resin and a polyethyleneimine resin;
[0071] The carbon dioxide adsorbent material 8 may be in a granular form or a powdered form;
[0072] The diameter of the carbon dioxide adsorbent 8 is 0.2 to 1.2 mm.
[0073] In this embodiment, the adhesive material 9 is one or more of polypropylene, polyethylene, and rubber, which has the characteristic of softening when heated, and can adhere the carbon dioxide adsorbent material 8 together in the softened state. The carbon dioxide adsorbent material 8 is a cross-linked primary amine resin or polyethyleneimine resin, which has the characteristics of large carbon dioxide adsorption and desorption capabilities. When the carbon dioxide adsorbent material 8 is in powder form, the formed mixed material 2 has a low porosity, and when the carbon dioxide adsorbent material 8 is in granular form, the formed mixed material 2 has a high porosity.
[0074] Furthermore, the amount of the carbon dioxide adsorbent material 8 accounts for 10 to 90% of the mass of the carbon dioxide adsorbent block;
[0075] There are gaps 10 between the carbon dioxide adsorbent materials 8, and the ratio of the volume of the gaps 10 to the volume of the carbon dioxide adsorbent block is called porosity;
[0076] Different sizes of granular or powdered carbon dioxide adsorbent material 8 affect the porosity.
[0077] In this embodiment, the amount of the carbon dioxide adsorbent material 8 is allowed to be between 10% and 90%. The more the amount of the carbon dioxide adsorbent material 8 is used, the better the adsorption and desorption effects are.
[0078] When the carbon dioxide adsorbent material 8 and the adhesive material 9 are mixed, there are gaps between the granular material and the powdery material. The larger the size of the granular material, the more gaps 10 are left. Therefore, the porosity can be controlled by mixing carbon dioxide adsorbent materials 8 and adhesive materials 9 of different sizes.
[0079] Further, a granular or powdered carbon dioxide adsorbent material 8 is selected according to the required porosity and mixed with a powdered binding material 9;
[0080] Hot air is blown into the mixed material 2 at a temperature of 180-200° C. for 10-40 seconds until the mixed material 2 is not melted as a whole but adheres to each other.
[0081] In this embodiment, the beneficial effect of using hot air to fuse the two materials is that the hot air can easily control the uniformity of heating, so that the mixed material 2 can be better achieved without melting the whole material 2 to be in a state of mutual adhesion. The method of using hot air to promote the mutual adhesion of the carbon dioxide adsorbent material 8 and the adhesive material 9 is called hot air molding method.
[0082] Reference Figure 2 As shown, step 2 uses an extrusion device, which includes a mesh plate 3, and a hot air blowing port 5 is arranged below the mesh plate 3;
[0083] The grids on the grid plate 3 meet the size requirements for the outflow to meet the block outflow;
[0084] Laying evenly mixed carbon dioxide adsorbent material 8 and adhesive material 9 on the grid plate 3;
[0085] The laid mixed material 2 is pressed downwards to make the mixed material 2 squeeze out from the grid;
[0086] Blow hot air to the extruded mixed material 2 until the mixed material 2 is not melted as a whole and adheres to each other;
[0087] A resistance wire 4 is arranged below the mesh plate 3 , and the resistance wire 4 cuts through the lower part of the mesh plate 3 in a heated state to perform thermal cutting on the extruded mixed material 2 .
[0088] In this embodiment, a hot air blowing port 5 is provided below the grid plate 3. After the mixed material 2 is extruded from the grid of the grid plate 3, it quickly enters a state of not melting as a whole and sticking to each other under the action of the hot air. In this state, the carbon dioxide adsorbent material 8 is adhered together by the adhesive material 9 to form a carbon dioxide adsorbent block with a porous structure. When the heating resistor wire 4 cuts through the mixed material 2 that is not melting as a whole and sticking to each other in the heated state, it is easy to cut it flatly to form a block material of the mixed material 2.
[0089] For further optimization, two heating resistor wires 4 are used for hot cutting.
[0090] In this embodiment, two heating resistance wires 4 cut the extruded mixed material 2, which can share the area swept by the cutting, and its beneficial effect is to shorten the hot cutting time and improve the hot cutting efficiency.
[0091] Further optimization, the mesh of the mesh plate 3 adopts circular holes;
[0092] The size of the circular hole is 4 to 6 mm;
[0093] The length of hot cutting is 3 to 4 mm.
[0094] In this embodiment, the grid adopts circular holes, which has the beneficial effect of being easy to process and reducing manufacturing costs.
[0095] Further optimization, a plastic mesh with elasticity is laid on the mesh plate 3;
[0096] Laying evenly mixed carbon dioxide adsorbent material 8 and adhesive material 9 on the plastic net;
[0097] The mixed material 2 laid on the plastic net is squeezed downward so that the plastic net wraps the mixed material 2 and squeezes it out of the mesh;
[0098] The heating resistance wire 4 is cut into the lower part of the mesh plate 3 to seal the mixed material 2 wrapped with the plastic mesh while cutting off the mixed material 2.
[0099] In this embodiment, an elastic plastic mesh is laid on the grid plate 3, and the mixed material 2 is laid on the plastic mesh. After hot cutting, the plastic mesh is coated on the outside of the mixed material 2. The beneficial effects are that, firstly, after coating with the plastic mesh, the gaps 10 between the blocks are increased, allowing air circulation to be smoother; secondly, the protection strength of the blocks is enhanced, making the blocks less likely to break; finally, the broken blocks can still maintain a block state under the coating of the plastic mesh, and will not break into tiny particles or even powder, resulting in blocking the gaps 10 for air circulation.
[0100] Reference Figure 2 As shown, the extrusion device includes a cavity for accommodating materials, and the cavity has a feed port 6 and a discharge port;
[0101] A flat plate moving toward the discharge port is also provided in the cavity, which is called an extrusion plate 1, and a telescopic mechanism 7 is connected to the back of the extrusion plate 1;
[0102] The discharge port is provided with a mesh plate 3;
[0103] A movable heating resistance wire 4 is also arranged below the grid plate 3;
[0104] At least two hot air blowing ports 5 are also arranged below the moving track of the heating resistance wire 4, and the at least two hot air blowing ports 5 are symmetrically arranged.
[0105] In this embodiment, the aperture of the grid holes on the grid plate 3 is used to limit the size of the block. The extrusion plate 1 is driven by the telescopic mechanism 7 to extrude the mixed material out of the grid holes. A hot air blowing port 5 is provided on the outside of the grid plate 3. The two hot air blowing ports 5 are symmetrically arranged, and the hot air is evenly distributed in the discharge port range. The extruded mixed material quickly enters a state of not melting as a whole and adhering to each other under the action of the hot air, so that the adhesive material 9 adheres to the carbon dioxide adsorption material 8 to form a block material with a porous structure.
[0106] Furthermore, in order to provide a concise description of exemplary embodiments, all features of an actual embodiment may not be described, ie, those features that are not relevant to the best mode of the invention or those features that are not relevant to implementing the invention.
[0107] It should be understood that in the development of any actual implementation, as in any engineering or design project, numerous implementation-specific decisions may be made. Such a development effort may be complex and time-consuming, but for those of ordinary skill having the benefit of this disclosure, the development effort will be a routine task of design, fabrication, and production without undue experimentation.
[0108] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a carbon dioxide adsorption block having a porous structure, characterized in that: The method for preparing the carbon dioxide adsorption block having a porous structure comprises the following steps: Step 1: Mix the bonding material and the carbon dioxide adsorbing material evenly; Step 2: Extrude the block shape; Step 3: Introduce hot air and blow until the adhesive material and the carbon dioxide adsorbent material are not melted as a whole but adhere to each other; Step 4: After hot cutting, cooling is performed to obtain a carbon dioxide adsorption block with a porous structure.
2. The method for preparing a carbon dioxide adsorption block having a porous structure according to claim 1, characterized in that: The adhesive material is one or more of polypropylene, polyethylene, and rubber; The bonding material is a powder material, and the diameter of the powder is 0.2 to 0.45 mm; The carbon dioxide adsorbing material is one or more of a cross-linked primary amine resin and a polyethyleneimine resin; The carbon dioxide adsorbent material may be in granular or powder form; The diameter of the carbon dioxide adsorbent is 0.2 to 1.2 mm.
3. The method for preparing a carbon dioxide adsorption block having a porous structure according to claim 1, characterized in that: The amount of carbon dioxide adsorption material used accounts for 10 to 90% of the mass of the carbon dioxide adsorption block; There are gaps between carbon dioxide adsorption materials, and the ratio of the gap volume to the volume of the carbon dioxide adsorption block is called porosity; Different sizes of granular or powdered carbon dioxide adsorbent materials affect the porosity.
4. The method for preparing a carbon dioxide adsorption block having a porous structure according to claim 3, characterized in that: Select a granular or powdered carbon dioxide adsorbent material according to the required porosity and mix it with a powdered binding material; Hot air is blown into the mixed material at a temperature of 180-200°C and maintained for 10-40 seconds until the mixed material is in a state where it does not melt as a whole but sticks to each other.
5. The method for preparing a carbon dioxide adsorption block having a porous structure according to claim 1, characterized in that: Step 2 uses an extrusion device, which includes a mesh plate with a hot air blowing port disposed below the mesh plate; The grid on the grid plate meets the size requirements of the outflow to meet the block outflow; Laying evenly mixed carbon dioxide adsorbent material and adhesive material on the grid plate; The laid mixed material is pressed downwards to squeeze the mixed material out of the grid; Blow hot air on the extruded mixed material until the mixed material does not melt as a whole and sticks to each other; A resistance wire is arranged below the mesh plate, and the resistance wire cuts through the lower part of the mesh plate in a heated state to perform thermal cutting on the extruded mixed material.
6. The method for preparing a carbon dioxide adsorption block having a porous structure according to claim 5, characterized in that: Two heating resistor wires are used for hot cutting.
7. The method for preparing a carbon dioxide adsorption block having a porous structure according to claim 5, characterized in that: The mesh of the grid plate uses circular holes; The size of the circular hole is 4 to 6 mm; The length of hot cutting is 3 to 4 mm.
8. The method for preparing a carbon dioxide adsorption block having a porous structure according to claim 5, characterized in that: An elastic plastic net is laid on the mesh plate; Laying evenly mixed carbon dioxide adsorbent material and adhesive material on the plastic net; The mixed material laid on the plastic net is squeezed downward so that the plastic net wraps the mixed material and squeezes it out of the mesh; A heating resistor wire is used to cut into the lower part of the mesh plate, and the mixed material wrapped with the plastic mesh is cut off and sealed at the same time.
9. The method for preparing a carbon dioxide adsorption block having a porous structure according to claim 5, characterized in that: The extrusion device includes a cavity for accommodating materials, and the cavity has a feed inlet and a discharge outlet; A flat plate is also provided in the cavity, which moves toward the discharge port and is called an extrusion plate. A telescopic mechanism is connected to the back of the extrusion plate. The discharge port is provided with a mesh plate; A movable heating resistance wire is also arranged under the grid plate; At least two hot air blowing ports are also arranged below the moving track of the heating resistance wire, and the at least two hot air blowing ports are symmetrically arranged.
10. A method for preparing a carbon dioxide adsorption block having a porous structure, characterized in that: The method for preparing the carbon dioxide adsorption block with a porous structure is to adopt the method for preparing the carbon dioxide adsorption block with a porous structure as claimed in any one of claims 1 to 9.